Steve Lieber's Favourite WebSites - Steve Lieber (ElectronicHealthcare, 2003)
Steve Lieber is President and CEO of the Chicago-based Healthcare Information and Management Systems Society (HIMSS), a leading association for healthcare IT professionals. Headquartered in Chicago, HIMSS provides services to more than 13,000 members, including IT healthcare corporations, firms and professionals from around the globe. Through the collaboration of 41 chapters and 20 special interest groups, HIMSS directs and shapes the healthcare industry, encourages emerging technology and promotes public policies that will improve healthcare delivery.